Quenching of Fluorescent ADS680HO molecule with Eco-Friendly Synthesized Silver Nanoparticles - Tangod, Vadiraj (The Nucleus, 2023)
In this work, we have collected spectroscopic optical fluorescence and absorption spectra of the highly fluorescent laser dye molecule ADS680HO in different spectroscopic grade solvents with and without the amalgamation of eco-friendly synthesized silver nanoparticles (AgNP’s), which resulted in the spectral intensities displaying quenching in the fluorescence and absorption intensities. It attributes the shape, dimension and bonding between the AgNP’s and ADS680HO molecules, as well as the transfer of energy among the fluorescent probe and AgNP’s. Fluorescence quenching of dye has innumerable uses for progress in cutting-edge bio-molecular labeling, fluorescence patterning and cancer treatment with chemotherapy.